The effectiveness of paradoxical therapy on relational practical obsessive-compulsive symptoms - Dehaqin, Vahideh; Besharat, Mohammad Ali; Gholamali Lavasani, Masoud; Naghsh, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Previous studies have shown that compared to the general population, patients with obsessive-compulsive disorder often have disorders in relational functioning, including interpersonal problems, mistrust, and unhappiness in interpersonal relationships, and the probability of marriage is lower and increased. Marital problems, ambivalence, severe interpersonal conflicts, revenge, and sexual problems are common. Thus, the present study aimed to determine the effectiveness of paradoxical therapy on relational practical obsessive-compulsive symptoms. Methods: In terms of the practical purpose and data collection method, the current research design was a single-case experiment of the multiple baseline type, sometimes called a single-subject experiment or a time series experiment. It is an experiment that consists of intensive research on a person or several people who are considered a single group. Among the single-subject designs, the baseline-intervention-follow-up (A-B-C) design was used in this study. The research community included all undergraduate, graduate, and doctoral students aged 20 to 45 years in Tehran. For sampling, six people were selected from the available sampling method and completed the treatment sessions. The clinical interview was used to diagnose the relational obsessive-compulsive disorder and its differential diagnoses. Quantitative data was collected by completing questionnaires and research scales in three phases: baseline, intervention, and follow-up. Results: The statistical analysis of the research data showed that the hypothesis of the research entitled "Paradoxical psychotherapy improves ego strength in relational obsessive-compulsive patients" was confirmed with 56.5% overall improvement. Conclusion: Based on the findings of the visual analysis of six participants and the results of the strong effect size and the improvement rate of relational obsessive-compulsive disorder symptoms, the results of the paradox treatment can be considered very effective.